Using The FMEA Method to Streamline Assembly of The Gearmotor - Michał SASIADEK; Waldemar WOZNIAK; Taras NAHIRNYJ (Communications of International Proceedings, 2022)
This article presents an analysis of the assembly process of the gearmotor, aimed at reducing the time taken to implement it and to eliminate the errors and bottlenecks occurring in selected technological operations for this purpose. To this end, measurements in operating time and the FMEA Method were used. Based on the analyses carried out, changes in the implementation of individual assembly operations were proposed and the resulting benefits have been estimated.
Keywords: Assembly; FMEA; motor reducer; streamline.